Global burden of thyroid cancer among adolescents and young adults, 1990-2021, and projections to 2050: an analysis based on the GBD 2021 - Jia, Ming-Jie; Wang, Shen; Li, Yu; Liu, Xing-Ning; Jiang, Feng; Li, Hui-Lin (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the global burden of thyroid cancer (TC) among adolescents and young adults (AYA) aged 15-39 years from 1990 to 2021, with projections to 2050, and identify demographic and regional disparities.MethodsUsing Global Burden of Disease (GBD) 2021 data, we analyzed incidence, prevalence, mortality, and disability-adjusted life years (DALYs) across 204 countries. Time-series projections to 2050 were generated using autoregressive integrated moving average (ARIMA) models.ResultsGlobal thyroid cancer incidence among AYA increased by 150% from 19,268 cases in 1990 to 48,203 in 2021, with persistent gender disparities: females exhibited a 2021 incidence rate of 2.38 per 100,000, threefold higher than males (0.88 per 100,000). Regional analysis revealed the highest burden in the Middle East and North Africa (2.49 per 100,000 in 2021). Projections indicate that by 2050, global prevalence will reach 103.62 per million, accompanied by an incidence rate of 11.41 per 100,000 and a DALYs burden of 34.41 per million, reflecting an 18% increase from 2021. Mortality rates show a modest rise from 0.37 per million in 1990 to a projected 0.42 per million in 2050. Socioeconomic disparities are pronounced: lower-Sociodemographic Index (SDI) regions face a projected 23% incidence increase by 2050, contrasting with a 12% decline in high-SDI regions, highlighting widening healthcare inequities.ConclusionThe growing burden of thyroid cancer among AYA populations demonstrates critical gender and geographic disparities, disproportionately affecting females and lower-resource regions. Mitigation requires enhanced early detection protocols, optimized treatment pathways, and targeted resource allocation to vulnerable populations.